Integrity control of masked database foreign key - Коломыцев, Михаил Владимирович; Носок, Светлана Александровна; Мазуренко, Анастасия Евгениевна (Ukrainian Information Security Research Journal, 2015)
The paper is about the actual problem of information protection in databases. The authors examine the method of data protection by masking. The essence of data masking is irreversible replacement of confidential information in the database (such as data identifying specific people) with non–sensitive data to prevent access of unauthorized users. Normally, the confidential data is replaced with data similar to real values that they can be used in the test systems with the assurance that the original data can not be obtained, extracted or recovered. Data masking involve replacing the initial confidential data (such as identifying specific people data) to other, hiding the original values. The masked data must remain functionally suitable for application processing (mainly testing problems, tuition, etc.). In this paper, the authors propose a method of static data masking through substitution, providing masking the primary key and foreign keys integrity of the database. This method is implemented as a stored procedure for data base management system (DBMS) MS SQL Server.